2004
DOI: 10.1017/s0022112003006529
|View full text |Cite
|
Sign up to set email alerts
|

On spray formation

Abstract: International audienceWe depict and analyse the successive steps of atomization of a liquid jet when a fast gas stream blows parallel to its surface. Experiments performed with various liquids in a fast air flow show that the liquid destabilization proceeds from a two-stage mechanism: a shear instability first forms waves on the liquid. The transient acceleration experienced by the liquid suggests that a Rayleigh–Taylor type of instability is triggered at the wave crests, producing liquid ligaments which furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

49
468
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 576 publications
(531 citation statements)
references
References 47 publications
49
468
1
1
Order By: Relevance
“…This result also agrees with the experimental results of Marmottant & Villermaux (2004) who plot the velocity profiles of an air jet injected into static air and again find that the shear layer in the jet is proportional to V −1/2 . The variation of β with V is much smaller than for δ 1 ; however it still increases with increasing V , and this variation has an effect on the breakup length calculations.…”
Section: Breakup Length Calculationssupporting
confidence: 91%
See 2 more Smart Citations
“…This result also agrees with the experimental results of Marmottant & Villermaux (2004) who plot the velocity profiles of an air jet injected into static air and again find that the shear layer in the jet is proportional to V −1/2 . The variation of β with V is much smaller than for δ 1 ; however it still increases with increasing V , and this variation has an effect on the breakup length calculations.…”
Section: Breakup Length Calculationssupporting
confidence: 91%
“…In the present study we examine how the growth rate at these saddles and their positions are affected when the interface between the two fluids is placed within the shear layer. We find that this leads to important qualitative differences compared with previous studies in which the density interface was assumed to lie on only one side of the shear layer (Marmottant & Villermaux 2004;Juniper 2007). Our assumption to neglect viscosity in this study is valid because Yu & Monkewitz (1990) showed that the transition to absolute instability is caused by the interaction between the two shear layers and is not a viscous effect.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…R-T generated turbulence also occurs in geophysical formations like salt domes and volcanic islands (DiPrima & Swinney 1981); in deep-sea ocean currents and in rivers and estuaries (Cui & Street 2004;Molchanov 2003). The breakup of fuel droplets in high speed flows have also been found to be R-T unstable (Marmottant & Villermaux 2004;Thomas 2003). Experiments performed to study atomization of a liquid jet when a fast gas stream blows parallel to its surface show that the liquid destabilization proceeds from a two-stage mechanism: a shear instability first forms waves on the liquid.…”
Section: Heavy Lightmentioning
confidence: 99%
“…Experiments performed to study atomization of a liquid jet when a fast gas stream blows parallel to its surface show that the liquid destabilization proceeds from a two-stage mechanism: a shear instability first forms waves on the liquid. The transient acceleration experienced by the liquid suggests that a Rayleigh-Taylor type of instability is triggered at the wave crests, producing liquid ligaments which further stretch in the air stream and break into droplets (Marmottant & Villermaux 2004). …”
Section: Heavy Lightmentioning
confidence: 99%